Unveiling Research Trends In Intensive Reading: A Bibliometric Perspective From 2019-2023 - Ismail, Hijril; Lukman, Lukman; Asbah, Asbah; Istianingsih, Sui (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sulawesi Tenggara, 2025)
The aim of the research is to offer a thorough analysis of the literature on intensive reading. The Publish or Perish software and the Scopus database were two of the sophisticated research methods used to find and compile a large number of pertinent academic publications and studies. In order to guarantee that the analysis is based on the most up-to-date and reliable research available, these resources were chosen for their effectiveness in locating high-quality, peer-reviewed papers. In this study, 37 publications published between 2019 and 2023 were thoroughly examined. Mendeley software was used to methodically organize and condense references, ensuring effective administration and simple access to relevant sources. Afterward, researchers used VOSviewer software to thoroughly examine the database in an effort to find trends and patterns among the articles. To provide a more organized summary of the existing literature on this topic, the researcher also attempted to classify the papers based on important themes, approaches, and conclusions. There are three clusters found. three components in Cluster 1: reading, the intensive care unit (ICU), and the neonatal intensive care unit (NICU). Staff and families must read and understand updates, directions, and charts for both units. The terms